Control of axonal growth and regeneration of sensory neurons by the p110delta PI 3-kinase. - Britta J Eickholt; Aminul I Ahmed; Meirion Davies; Evangelia A Papakonstanti; Wayne Pearce; Michelle L Starkey; Antonio Bilancio; Anna C Need; Andrew J H Smith; Susan M Hall; Frank P Hamers; Karl P Giese; et al. (PLoS ONE)
The expression and function of the 8 distinct catalytic isoforms of PI 3-kinase (PI3K) in the nervous system are unknown. Whereas most PI3Ks have a broad tissue distribution, the tyrosine kinase-linked p110delta isoform has previously been shown to be enriched in leukocytes. Here we report that p110delta is also highly expressed in the nervous system. Inactivation of p110delta in mice did not affect gross neuronal development but led to an increased vulnerability of dorsal root ganglia neurons to exhibit growth cone collapse and decreases in axonal extension. Loss of p110delta activity also dampened axonal regeneration following peripheral nerve injury in adult mice and impaired functional recovery of locomotion. p110delta inactivation resulted in reduced neuronal signaling through the Akt protein kinase, and increased activity of the small GTPase RhoA. Pharmacological inhibition of ROCK, a downstream effector of RhoA, restored axonal extension defects in neurons with inactive p110delta, suggesting a key role of RhoA in p110delta signaling in neurons. Our data identify p110delta as an important signaling component for efficient axonal elongation in the developing and regenerating nervous system.